EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIALKELAS IV DI UPTD SD NEGERI TAWALI - Kasianus Malaikalong; Yessy Mata; Jon A. Lalang Yame (CV. ADIBA ASIHA AMIRA, 2026)
The aim in the study was to ever use the use of the learning media of Mind Mapping on the results of default Jar students in the subjects of the Grade IV of Natural and Social Sciences at UPTD SD Negeri Tawali by using Mind Mapping learning media in IPAS learning. The type of research used in the study is a type of quantitative research a pre-experimental approach was carried out with the One Group Pretest at the beginning and posttest at the end with a sample size of 21 students. The subject in this study was class IV students at UPTD to Tawali. Researchers collect data from results using data collection techniques for instrument validation, tests and questionnaires. Before testing the material feasibility test and the feasibility of the media through validity tests of 83 and 76, the reliability test of 0.80, the pretest of 56.19 and the posttest of 85.23, the prerequisitory test was carried out by the normality of 0.068. After that test was tested with a hypothesis test using a paired test sample t-test after that data was analyzed using SPSS 22 help and got the results of the thit 22,029 and TTAB 1.725 meaning the thith> TTAB then H0 was rejected and H1 was accepted.